Avaliação de competências profissionais de aprendizes com deficiência - Zanote, Marco Aurélio; Manzini, Eduardo José [UNESP] (My University, 2012)
Professional competence can be one of the paths for the insertion of the disabled students in the labor market. This study evaluated the development of skills from the perspective of five learners with disabilities, their tutors and teachers. The survey was conducted in a non-governmental organization that had a range of 32 skills to be taught. The assessment revealed that some of the skills improve with provided training, others remained at the same level and only one decreases its score. It is possible to conclude that the learning program contributed to the development of the skills, which may mean the inclusion of young people in the labor market.

A competência profissional pode ser um dos caminhos para a inserção do aprendiz com deficiência no mercado de trabalho. O presente estudo avaliou o desenvolvimento de competências profissionais na perspectiva de cinco aprendizes com deficiência, seus tutores e professores. A pesquisa foi realizada em uma organização não governamental que possuía uma matriz de 32 competências a serem desenvolvidas. A avaliação revelou que algumas das competências melhoram com o treinamento oferecido, outras se mantiveram no mesmo nível e apenas uma diminui o seu escore. Conclui-se que o programa de aprendizagem contribuiu para o desenvolvimento de competências, o que pode significar a inclusão desses jovens no mercado de trabalho.
Evaluation of professional skills of apprentices with disabilities
Keywords: Educacao Especial; Profissionalização do deficiente